Feeling unwell, "so was their due" : women and their perception of health in Mexico - Isabel Hernández Tezoquipa; María de la Luz Arenas Monreal; Rosario Váldez Santiago (Universidad de Alicante, 2012)
Objective: To analyse the implicit social process between feeling unwell and seeking for health services help, in women from five Mexizan regions. Material and methods: Forty interviews to women aged 35-65 years within the National Health Survey 1994 were qualitatively analysed. These women came from five different Mexican regions: a metropolitan area, the north, the south, the centre and a depressed area. Results: Research findings show that women's perception of health is about "feeling constantly unwell"; nevertheless, they do not "lay on bed". The seek for health services help is always a late one, due to the role they play as social reproducers within their families and communities. Conclusion: Health professionals' knowledge about women's experiences regarding their perception and health care, will allow them to become aware of the reasons for these women's late seek for health services help.